Upaya Hukum dalam Meningkatkan Pendapatan Asli Daerah (Studi di Kecamatan Tanjungkarang Pusat). - Agus Iskandar (PRANATA HUKUM, 2016)
Handling and management of land and building tax (PBB) is expected to lead administration and is able to increase community participation in development financing. The problem in this research is legal action taken by the Office of the District Tanjung Karang, Bandar Lampung Center to Improve Regional own source Revenue. Digunaka approach to the problem is normative and empirical approach. Data collection techniques with literature studies and field studies. Qualitative analysis. The result of research that attempts increase revenue in Bandar Lampung with the implementation of the strategy of local tax collection system by the establishment of the Regional Head (official assessment system) and in a way paid by the taxpayer (self assessment system). Suggestions put forward so that the rate of tax and levies to be reconsidered because it increases the tax rat e and levy will not necessarily result in increased revenue.